Multi-stimuli-responsive fluorescence of axially chiral 4-ene-β-Diketones. (January 2021) - Wu, Dehua; Fang, Xinyi; Song, Jintong; Qu, Lang; Zhou, Xiangge; Xiang, Haifeng; Wang, Jun; Liu, Jin
Abstract: A unique series of simple, smart, and chiral binaphthalene-substituted 4-ene-β-diketones molecules has been designed and prepared. Their optical properties, charge contribution, and transition process highly depend on their chemical structures. These π-conjugated materials are highly emissive in both solution and solid (emission quantum yield up to 68%), owing to the inhibition of enol-keto tautomerization and the effect of steric hindrance from binaphthalene. Through ethylenic bond hydrolysis, they can be used for not only cation/anion sensing but also chiral amino acids recognition. Moreover, at low concentrations, they have little cytotoxicity to living cells and can stain cytoplasm. Therefore, they afford a new platform in the design of multi-stimuli-responsive, smart, and chiral materials. Graphical abstract: Through hydrolysis, simple alkene-linked binaphthalene-β-diketones molecules show multi-stimuli-responsive fluorescence for not only cation/anion but also chirality recognition. Image 1 Highlights: It is still challengeable to prepare highly emissive binaphthalene-based materials. These π-conjugated materials are highly emissive in both solution and solid with large Stokes shifts (emission quantum yield up to 68% and Stokes shift up to 145 nm), owing to the inhibition of enol-keto tautomerization and the effect of steric hindrance from binaphthalene. To the best of our knowledge, they are the first examples for cation/anion and chirality recognition through ethylenic bond hydrolysis.